IMPLEMENTASI PERMAINAN TRADISIONAL BALAP KARUNG DALAM MENINGKATKAN AKTIVITAS FISIK ANAK DI PANTI ASUHAN JIREH SEMENIFESTARA - Heka Maya Sari Sembiring; Ayu Winda Rajagugkguk; Milkalia Br Kaban; Rumondang Situmorang; Enjelia Sihite; Martha Carolina Br Tarigan (ASOSIASI IDEBAHASA KEPRI, 2026)
Physical activity plays a crucial role in supporting children's overall growth and development, including physical, social, and emotional development. Children living in orphanages often have limited access to structured and enjoyable physical activities. This study aims to analyze the implementation of the traditional sack race game in increasing children's physical activity at the Jireh Semenifestara Orphanage. The study used a qualitative approach with descriptive methods. The subjects were children aged 7–12 years who participated directly in the sack race game. Data were collected through observation of children's activities during the game, interviews with the orphanage caregivers, and documentation of the activities. The results indicate that the traditional sack race game can increase children's physical activity, train muscle strength, balance, and motor coordination, and foster values of sportsmanship, cooperation, and self-confidence. Therefore, the traditional sack race game can be used as an effective alternative educational and recreational activity to increase children's physical activity in orphanages.